2002
DOI: 10.1093/ejo/24.2.191
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two mandibular advancement appliances for the treatment of obstructive sleep apnoea

Abstract: Mandibular advancement appliances (MAAs) are accepted as a treatment option for snoring and mild obstructive sleep disorders. In the present clinical study two differently designed devices were examined for their effectiveness in treating obstructive sleep apnoea (OSA). The study was based on an assessment of 26 patients with a polysomnographic diagnosis of mild OSA [22 men, four women; mean body mass index 27.3 kg/m2 (SD 3.1); mean age 56.8 years (SD 5.2); mean respiratory disturbance index (RDI): 16.0 events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
1
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 12 publications
3
99
1
9
Order By: Relevance
“…The RCTs evaluated the effects of MADs compared with placebo treatment [11,13,14,22,23,25,[28][29][30], CPAP [11, 13, 16-19, 24, 26, 32, 34] or between appliance designs [15,20,27,31,33,35,36,38]. Three studies reported longer-term results from MAD treatment after 1-4 yrs, compared with CPAP [12], surgery [37] or between two types of MAD [21].…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The RCTs evaluated the effects of MADs compared with placebo treatment [11,13,14,22,23,25,[28][29][30], CPAP [11, 13, 16-19, 24, 26, 32, 34] or between appliance designs [15,20,27,31,33,35,36,38]. Three studies reported longer-term results from MAD treatment after 1-4 yrs, compared with CPAP [12], surgery [37] or between two types of MAD [21].…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Patients included in the RCTs had mild to severe OSA [13,14,17,18,20,[24][25][26][27][29][30][31][32][33][34][35][36][37][38], with mean AHI or RDI of 10-50. With MADs, AHI or RDI decreased to mean values of 4.5-34, which corresponded to reductions in the frequency of respiratory disturbances of means of 28-80% (mean reduction from all studies of 55%).…”
Section: Effects On Osamentioning
confidence: 99%
See 1 more Smart Citation
“…Com a utilização habitual do dispositivo, os pacientes que chegaram ao final do tratamento foram encaminhados para uma nova polissonografia, a qual foi realizada com o paciente fazendo o uso do aparelho ortopédico Bionator de Balters para avaliar e quantificar a eficácia deste dispositivo no tratamento do ronco e da apnéia. Observou-se melhora estatisticamente significante em relação ao IDR (índice de distúrbio respiratório), mostrando a efetividade deste dispositivo e corroborando outros estudos 1,9,12,13,15,17,26,33 que também utilizaram dispositivos intrabucais para o tratamento da SAOS. Este exame, assim como no inicial, realiza uma monitorização das características do sono em condições o mais próximo possível das normais e semelhantes às do paciente em sua casa.…”
Section: Discussionunclassified
“…AveoTSD, or "Tongue Stabilizing Device" The aveoTSD is made from a soft medical silicone for comfort and works by holding the tongue forward by gentle suction preventing it from falling back against the back of the throat, keeping the airway open during sleep (George et al, 1987;Schmidt-Nowara et al, 1991;Meyer-Ewert et al, 2002;Wade, 2003;Chen et al, 2012). (Ferguson et al, 2006;Chan et al, 2007;Ogawa et al, 2015;Ballanti et al, 2015).…”
mentioning
confidence: 99%